Modelling the Dependence Structure between Australian Equity and Real Estate Markets – a Copula Approach - Ning Rong; Stefan Trück (Australasian Accounting, Business and Finance Journal, 2014)
Over the last decades, the Australian market for Real Estate Investment Trusts (REITS) has shown substantial growth rates. We apply conditional copula models in order to investigate the dependence structure between the returns from REITS and equity markets in Australia. The dependence between these assets has a significant impact on the diversification potential and risk for a portfolio of multiple assets and is therefore of great interest to portfolio managers and investors. We compare the suggested copula models to a standard variance-covariance approach and a Dynamic Conditional Correlation (DCC) model. We observe significant positive correlations between the considered series. The level of correlation has also increased during the last decade indicating a limited diversification potential of investments in REITS for Australia markets. We also find tail dependence between the examined series that is best modelled by the Student t copula. Finally, we conduct a back-testing Value-at-Risk study for a portfolio that combines investments in real estate and equity. We find that the conditional copula approach outperforms both a static variance-covariance approach and the DCC model with respect to quantifying the risk of extreme negative returns. Our findings suggest that ignoring the complex and dynamic dependence structure in favour of a simple multivariate normal model leads to a significant underestimation of the actual risk.
Keywords: REITS; Dependence Structure; Dynamic Conditional Correlations; Copula Models; Time-Varying Copulas; Risk Analysis